Sustainable communities - Hanlon, Bill (Kansas State University, 2010)
Local governments, counties, and regional planning entities throughout the US have been developing new strategies and implementation plans for sustainability. Sustainability planning often integrates areas such as green building standards, urban redevelopment and regeneration districts, smart growth policies, public and pedestrian/bike friendly transportation, local food supply and area food policies, and more. This panel will discuss major trends and needs for sustainable communities in Kansas as well as how higher education is involved and how it can be more involved.
Keywords: Sustainable communities; Energy efficiency; Green building; Sustainable design; Energy efficient construction